Islam dan Nasionalisme: Analisis Atas Pemikiran 'AIi 'Abd al-Raziq - Ahmad Junaidi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2007)
This study aims to analyze 'Ali 'Abd al-Raziq's thoughts on the relationship between Islam and nationalism, especially in the context of the dissolution of the Ottoman Caliphate. This study explores al-Raziq's arguments that reject the concept of caliphate-based Islamic politics and support the separation of religion and state. The method used is library research with a descriptive-analytical approach to al-Raziq's main work, Al-Islam wa Usul al-Hukm, as well as academic literature discussing the response of scholars to his ideas. The results show that al-Raziq argues that Islam is a spiritual religion that does not have a specific system of government, so that the state can be built based on the principles of modern nationalism. His views sparked heated debate among Muslim scholars and intellectuals. This study emphasizes that al-Raziq's thinking contributed to the discourse of Islamic politics and is relevant to the debate on the relationship between religion and the state. nationalism; 'Ali 'Abd al-Raziq; caliphate; Islamic politics.